Authorizing Early Modern European Women: From Biography to Biofiction - Fitzmaurice, James; Miller, Naomi J.; Steen, Sara Jayne (Gendering the Late Medieval and Early Modern World, 2021)
The essays in this volume analyze strategies adopted by contemporary novelists, playwrights, screenwriters, and biographers interested in bringing the stories of early modern women to modern audiences. It also pays attention to the historical women creators themselves, who, be they saints or midwives, visual artists or poets and playwrights, stand out for their roles as active practitioners of their own arts and for their accomplishments as creators. Whether they delivered infants or governed as monarchs, or produced embroideries, letters, paintings or poems, their visions, the authors argue, have endured across the centuries. As the title of the volume suggests, the essays gathered here participate in a wider conversation about the relation between biography, historical fiction, and the growing field of biofiction (that is, contemporary fictionalizations of historical figures), and explore the complicated interconnections between celebrating early modern women and perpetuating popular stereotypes about them.